2002
DOI: 10.1038/sj.bjc.6600471
|View full text |Cite
|
Sign up to set email alerts
|

A model for co-expression pattern analysis of genes implicated in angiogenesis and tumour cell invasion in cervical cancer

Abstract: To date, numerous genes have been identified which are involved in both tumour neovascularisation (angiogenesis) and tumour cell invasion, and most of them are also expressed to some extent under normal physiological conditions. However, little is known about how these genes co-express in these settings. This study was undertaken to quantitate mRNA levels in normal and malignant cervical tissues of nine selected genes (VEGF 121 , VEGF 165 , VEGF 189 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 45 publications
2
42
0
4
Order By: Relevance
“…We did not observe an association between bFGF-expressing cells with the number of CD105 (or CD31)-positive vessels. An increase in bFGF mRNA expression has been reported during cervical tumour development (Fujimoto et al, 1997;Van Trappen et al, 2002), whereas a decrease in bFGF expression was reported in the study of Soufla et al (2005). To our knowledge, our study is the first study on bFGF-expressing cells in cervical carcinoma at the protein level using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 75%
“…We did not observe an association between bFGF-expressing cells with the number of CD105 (or CD31)-positive vessels. An increase in bFGF mRNA expression has been reported during cervical tumour development (Fujimoto et al, 1997;Van Trappen et al, 2002), whereas a decrease in bFGF expression was reported in the study of Soufla et al (2005). To our knowledge, our study is the first study on bFGF-expressing cells in cervical carcinoma at the protein level using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 75%
“…Similar to AKT, MMP3 can also cause epithelial -mesenchymal transition in cancer (Radisky et al, 2005). Matrix metalloproteinase 9 plays a central role in connective tissue degradation, tumourinduced angiogenesis, cell proliferation/apoptosis and cell migration in various tumour types including cervical cancer (van Kempen and Coussens, 2002;Van Trappen et al, 2002;Zucker and Vacirca, 2004;Vazquez-Ortiz et al, 2005b). Recently, one study has shown that MMP9 forms a complex with the hyaluronan receptor CD44 on the surface of breast cancer cells and activates downstream TGF-b, facilitating tumour cell survival, invasion and metastasis (Yu and Stamenkovic, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These studies could direct new therapeutic strategies targeting specific candidate genes. Although a variety of genes have been implicated in cervical cancer invasion, migration and lymph node metastasis, most studies have used only cervical cancer cell lines or primary tumours (Shim et al, 1998;Ruutu et al, 2002;Van Trappen et al, 2002;Vazquez-Ortiz et al, 2005a). To our knowledge, no data are available on gene expression profile differences between primary tumours and matched metastatic or recurrent tumours in cervical cancer.…”
mentioning
confidence: 99%
“…VEGF is expressed and secreted by tumor cells in response to hypoxia, which contributes to tumor expansion associated with neovascularization (Barleon et al, 1997). Interestingly, the VEGF gene is upregulated in most types of cancers (Nakamura et al, 2002;Van Trappen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%